A Feminist Carnivalesque Ecocriticism: The Grotesque Environments of Barbara Gowdy’s Domestic Fictions - Lousley, Cheryl (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2014)
This comparative examination of Canadian writer Barbara Gowdy’s fiction, specifically the novels Falling Angels (1989), Mister Sandman (1996), The Romantic (2003), and Helpless (2007), and several short stories in We So Seldom Look on Love (1992), expands the study of the feminist grotesque from representations and performances of transgressive bodies to the politics involved in imagining and inhabiting grotesque environments. Gowdy’s fiction makes freaks ordinary through domestic realism, and in so doing her narratives make strangely surreal the “normal” environments of late modernity. By imagining our bodies and environments as grotesque forms — uneven and ungainly, open and porous, incomplete and excessive — Gowdy’s depictions of freaks and their ordinary domestic and suburban environments broadly entail a carnivalesque inversion of normative environments that has social and ecological relevance. The normative home is figured by way of miniaturizing containers that restrict — albeit only partially — gender, sexuality, and physical embodiment to normative practices and symbolically exclude ecological processes in an illusion of self-enclosure. Gowdy’s carnivalesque inversions show ordinary residential environments to be dense with animal lives and deaths, energy flows, and fungal and vegetative growth and decay. The recurring theme of power outages and electricity transmission lines shows seemingly self-contained domestic space supported by an extensive industrial infrastructure, and socially marginal women absurdly imagining themselves responsible for industrial failures in primarily masculine domains. Gowdy’s carnivalesque domestic realism historically situates suburban development, nuclear families, and nuclear weaponry as a particular set of gendered social relations while resisting any reduction of the physical world to an inert background.